RELATIONSHIP BETWEEN ANAEMIA AND SIMPLE FEBRILE CONVULSIONS - Sultan, Ambreen; Fayaz, Muhammad; Khan, Abdul Najeeb; Fayaz, Afnan (Journal of Ayub Medical College Abbottabad, 2013)
Background: Simple febrile seizures are the commonest convulsions occurring in children and its exact pathophysiology is unknown. Among other postulated reasons anaemia has been thought to be a possible aetiology. This study was conducted to find out any relationship between anaemia and simple febrile convulsions. Methods: We studied notes of 1,951 patients retrospectively who were admitted in the Women & Children Hospital Abbottabad from Jan 2013 to Aug 2013. Thirty-one patients with febrile seizures were included in the study as group I and another 31 patients matched for the demographic data were taken as group II. Degree of temperature, family history of simple febrile convulsions, underlying focus of infection and haemoglobin level were recorded. Results: Sixty-eight percent of patients in group I had Hb level below 11 gm/dl compared to 39% of patients in group II; 32% patients of group I, had level on/above 11 gm/dl but none of them had Hb above 11.5 gm/dl in comparison to group II where 61% had Hb level on/above 11 gm/dl with upper limit of 13 gm/dl. Conclusion: Significant association was found between anaemia and Simple Febrile Convulsions. Keywords: Simple Febrile Convulsions, Haemoglobin, iron deficiency, treatment, temperature